Molecular energetics of alkyl substituted pyridine N-oxides An experimental study - Joana I. T. A. Cabral (2010)
The standard (p(o) = 0.1 MPa) energies of combustion in oxygen, at T = 298.15 K, for the solid compounds 2-methylpyridine-N-oxide (2-MePyNO), 3-methylpyridine-N-oxide (3-MePyNO) and 3,5-dimethylpyridine-N-oxide (3,5-DMePyNO) were measured by static-bomb calorimetry, from which the respective standard molar enthalpies of formation in the condensed phase were derived. The standard molar enthalpies of sublimation, at the same temperature, were measured by Calvet microcalorimetry. From the standard molar enthalpy of formation in gaseous phase, the molar dissociation enthalpies of the N-O bonds were derived, and compared with values of the dissociation enthalpies of other N-O bonds available for other pyridine-N-oxide derivatives.